INDIA’S COMPLIANCE WITH INTERNATIONAL HUMAN RIGHTS STANDARDS IN THE ENFORCEMENT OF CRIMINAL LAW - Sneha Madhuri Chatterjee; Aditya Prakash Mehta; Ananya Priya Sharma; Karthik Narayanan Iyer; Ishita Neelam Verma; Vikram Ananth Rao; Rohan Suresh Patel (International Journal of Education and Social Science Studies, 2026)
This study examines India’s compliance with international human rights standards in the enforcement of criminal law, by addressing the extent to which institutional practices align with international human rights obligations and identifying key factors that hinder such compliance. Despite India’s ratification of major international instruments such as the International Covenant on Civil and Political Rights (ICCPR) and the incorporation of human rights protections in its Constitution, significant gaps persist between legal norms and practical implementation. The study employs a normative and empirical analysis approach, through doctrinal legal analysis combined with descriptive statistical evaluation of secondary data, and relevant scholarly literature to using a three-tier compliance framework consisting of normative, institutional, and outcome dimensions. Key findings reveal that India’s prisons are severely overcrowded, with average occupancy rates of 131% and some facilities exceeding 400%, adversely affecting access to basic amenities, healthcare, and rehabilitation programs. Additionally, approximately 76% of prisoners are undertrial detainees, reflecting prolonged pre-trial detention and systemic inefficiencies that undermine the presumption of innocence. Custodial deaths and instances of torture further highlight gaps in enforcement and oversight, disproportionately affecting marginalized populations. The study identifies a persistent norm-implementation gap, wherein legal frameworks exist but are inadequately enforced due to structural and institutional weaknesses. These findings underscore the urgent need for comprehensive reforms while also contributing to the development of an integrated framework for evaluating human rights compliance in criminal justice systems, including modernization of prison infrastructure, expedited judicial processes, strengthened monitoring mechanisms, systematic human rights training for law enforcement, and equitable access to legal aid. The study concludes that addressing these challenges is essential not only for India’s compliance with international human rights obligations but also for establishing a more equitable, effective, and humane criminal justice system that protects the rights and dignity of all individuals.